Vanillic acid and methoxyhydroquinone production from guaiacyl units and related aromatic compounds using Aspergillus niger cell factories - Lubbers, Ronnie J. M.; Dilokpimol, Adiphol; Nousiainen, Paula A.; Cioc, Răzvan C.; Visser, Jaap; Bruijnincx, Pieter C. A.; de Vries, Ronald P. (Microbial cell factories, 2021)
Background The aromatic compounds vanillin and vanillic acid are important fragrances used in the food, beverage, cosmetic and pharmaceutical industries. Currently, most aromatic compounds used in products are chemically synthesized, while only a small percentage is extracted from natural sources. The metabolism of vanillin and vanillic acid has been studied for decades in microorganisms and many studies have been conducted that showed that both can be produced from ferulic acid using bacteria. In contrast, the degradation of vanillin and vanillic acid by fungi is poorly studied and no genes involved in this metabolic pathway have been identified. In this study, we aimed to clarify this metabolic pathway in Aspergillus niger and identify the genes involved. Results Using whole-genome transcriptome data, four genes involved in vanillin and vanillic acid metabolism were identified. These include vanillin dehydrogenase ( vdhA ), vanillic acid hydroxylase ( vhyA ), and two genes encoding novel enzymes, which function as methoxyhydroquinone 1,2-dioxygenase ( mhdA ) and 4-oxo-monomethyl adipate esterase ( omeA ). Deletion of these genes in A. niger confirmed their role in aromatic metabolism and the enzymatic activities of these enzymes were verified. In addition, we demonstrated that mhdA and vhyA deletion mutants can be used as fungal cell factories for the accumulation of vanillic acid and methoxyhydroquinone from guaiacyl lignin units and related aromatic compounds. Conclusions This study provides new insights into the fungal aromatic metabolic pathways involved in the degradation of guaiacyl units and related aromatic compounds. The identification of the involved genes unlocks new potential for engineering aromatic compound-producing fungal cell factories.